DEVELOPING DIGITAL LEARNING APLICATION AS A LEARNING MEDIA FOR DEAF STUDENTS IN LEARNING ENGLISH VOCABULARY - Pratama, Putra; Destia Dwi Mulyani (Universitas PGRI Palembang, 2025)
This research aims to create digital-based English learning media tailored for deaf children. The study employs the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation. A needs analysis was conducted to assess the current challenges faced by deaf students in learning English through digital media. The findings highlight several key issues, including a shortage of qualified English teachers, reliance on text-based teaching materials, and an ineffective learning process due to the predominant use of textbooks, which are less suitable for visual learners like deaf students. Consequently, developing digital learning media is crucial. The learning media designed in this study is an Android-based digital application incorporating images, animations, and videos to create a more engaging learning experience, making it easier for both teachers and students to teach and understand English. The study's results indicate that the digital English learning media application effectively enhances students’ comprehension of English.